(3OjhGf eLfhf Hfj YGeQ hCNHGQgs - (3eLfhf djdj , bjS Hf GdedhM Hf eRGMe GdYGeQj,J (B68 (3g` s
(3ChdgG (B:s
(3bGd(B: (3cGf ef MOjKg Cfg cGf UZjQkG hdjdi UZjQI hcGfG jLJeYGf aj Hge ajg dgeG jJMOKGf adeG THG hcHQG LYd MHgeG jfei hjRjO cd SGYI s
(3BNQgG (B:s
(3agPI LedI eG JfGgi EdjfG ef CNHGQ GdeLfhf hCTYGQg, heG cGf NGQLkG YeG de fcJHg aEfgG efMhdI Ydjg ef bUjOI Ch NHQ, hGddg JHGQc hJYGdi CYde s
(3GfXQ GdLRA GdChd HQbe (B349 (3COH HYfhGf OjhGf bjS Hf GdedhMs
(3hQO CjVkG JMJ Qbe (B"10" (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B208s
Keywords: (3GdCOHs